An Analysis of Code-Switching by College Students in Makassar - Marwah Juwita Yusuf; Indrayani Simpuruh; Syamsinar Syamsinar (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study examines code-switching among college students in Makassar, Indonesia. Code-switching, defined as the practice of alternating between two or more languages in a single conversation, is a common phenomenon in bilingual and multilingual communities. With the increasing influence of English in Indonesian education, students frequently switch between Indonesian and English. This research aims to identify the types of code-switching, understand its functions, and explore the reasons behind this linguistic behavior among college students. Data were gathered through recorded conversations and semi-structured interviews with 50 participants from different universities in Makassar. The results show that intra-sentential code-switching is the most prevalent, and the practice is influenced by social context, language proficiency, and exposure to digital media. This study provides significant insights into the bilingual language practices of college students in Makassar, specifically highlighting how code-switching serves as a dynamic tool for social interaction, identity negotiation, and academic expression. The findings contribute to a deeper understanding of bilingual practices in Southeast Asia and provide practical insights for educators, suggesting that embracing multilingualism in academic contexts can create more inclusive and effective learning environments.